Conventional testicular sperm extraction (TESE) and non‐obstructive azoospermia: is there still a chance in the era of microdissection TESE? Results from a single non‐academic community hospital. (12th February 2016) - Saccà, A.; Pastore, A. L.; Roscigno, M.; Naspro, R.; Pellucchi, F.; Fuschi, A.; Maruccia, S.; Territo, A.; Pisano, F.; Zanga, L.; Capitanio, E.; Carbone, A.; et al.
Summary: Spermatozoa can be retrieved in non‐obstructive azoospermia (NOA) patients despite the absence of ejaculated spermatozoa in their semen because of the presence of isolated foci with active spermatogenesis. Conventional testicular sperm extraction (c‐TESE) in patients with NOA has been partially replaced by micro‐TESE. It is still under debate the problem regarding the higher costs related to micro‐TESE when compared with c‐TESE. In this study, we evaluated sperm retrieval rate (SRR) of c‐TESE in naive NOA patients. Sixty‐three NOA patients were referred to our centre for a c‐TESE. For every subject, we collected demographic data, cause of infertility, time to first infertility diagnosis, serum levels of LH, FSH, total testosterone and prolactin. A statistical analysis was conducted to correlate all the clinical variables, the histology and the Johnsen score with the SRR. Sixty‐three consecutive NOA patients with a mean age of 37.3 years were included. The positive SRR was 47.6%. No statistical differences were observed between positive vs. negative SRR regarding mean FSH (17.12 vs. 19.03 mUI/mL; p = 0.72), and LH (9.72 vs. 6.92 mUI/mL; p = 0.39) values. Interestingly, we found a statistically significant difference in terms of time to first infertility diagnosis (+SRR vs. −SRR; 44.5 vs. 57 months; p = 0.02) and regarding to age (+SSR vs. −SRR; 40.1 vs. 35.3; p = 0.04). There was a statistically significant decrease in SRRs with the decline in testicular histopathology from hypospermatogenesis to maturation arrest, and SCO. The mean Johnsen score was 5.9 with a mean percentage of Johnsen score ≥8 tubules equal to 19%. The overall pregnancy rate was 26.6%. In our prospective cohort of patients successful SRR with c‐TESE was 47.6%. Lower costs and high reproducibility of this technique still support this procedure as an actual reliable option in NOA patients for sperm retrieval.